Factors Affecting Work Efficiency of Personnels of Ubonratchathani Primary Educational Service Area office 5 - Pimpang, Cheewarat; Phorncharoen, Irada; Phorncharoen, Irada; Unchai, Thitiphon (Journal of Human and Society, Sisaket Rajabhat University, 2022)
The purposes of this study were 1) to study the factors affecting work efficiency of personals of Ubon Ratchathani Primary Educational Service Area office 5 and 2) to compare factors affecting work efficiency of personnel of Ubon Ratchathani Primary Educational Service Area office 5 classified by demographic characteristics. Three hundred sixty-five personals were selected by Proportional Stratified Random Sampling (by referring to Taro Yamane, 1973: 727). The research instruments used for data collection was a 5-point scale questionnaire with the validity level of 0.92. The percentage, mean, standard deviation, multiple regression analysis, T-test, and F-test were used to analyze the data. The results of the study were as follows 1) In terms of values, strategy, systems, job characteristics and the organizational culture affecting work efficiency of personals of Ubon Ratchathani Primary Educational Service Area office 5 can jointly predict work efficiency of personnel of Ubon Ratchathani Primary Educational Service Area Office 5 by 38.10 percent (R2adj= .381) 2) Personals with different ages valued the organizational culture and job characteristics significantly different at the statistical level of .01, and the shared values significantly different at the statistical level of .05. personals with different level of education gave precedence to the organizational culture and job characteristic significantly different at the statistical level of 0.5. personnel with type of positions placed importance on job characteristics, strategies, systems, and shared values significantly different at the statistical level of 0.5.